Mediated millennials - Schulz, Jeremy; Robinson, Laura; Khilnani, Aneka; Baldwin, John; Pait, Heloisa; Williams, Apryl A.; Davis, Jenny; Ignatow, Gabe (Emerald Publishing Limited, 2019)
Sponsored by the Communication, Information Technologies, and Media Sociology section of the American Sociological Association (CITAMS), Volume 19 of Emerald Studies in Media and Communications draws on global case studies that examine media use by millennials. By bringing together contributors and case studies from four continents to examine millennial digital media practices, the volume charts out multiple dimensions of Gen Y's digital media engagements: smartphone use among Israelis, the activities of Brazilian youths in LAN houses, selfies in the New Zealand context, and American millennials engaged in a variety of digital pursuits ranging from seeking employment, to content creation, to gaming, to consuming news and political content. Through these case studies we see parallels in the mediated millennial experience across key digital venues including Twitter and YouTube, and MMOs. None-the-less, contributors also prompt us to keep in mind the importance of those millennials without equal access to resources who must rely on public venues such as libraries and LAN Houses. Across these venues and arenas of practice, the research provides an important collection of research shedding important light on the first generation growing up with the normative expectation to perform digital identity work, create visual culture, and engage in the digital public sphere.
Includes index.
Keywords: Social media.; Generation Y.; Social Science -- Media Studies.; Society & culture: general.; elektronické knihy; electronic books